A Flame‐Reaction Method for the Large‐Scale Synthesis of High‐Performance SmxCoy Nanomagnets. (4th September 2019) - Ma, Zhenhui; Tian, Hui; Cong, Liying; Wu, Qiong; Yue, Ming; Sun, Shouheng
Abstract: We report a flame‐reaction method to synthesize high‐performance Sm x Co y ( x =1, y =5; x =2, y =17) particles on a multigram scale. This flame reaction allows the controlled decomposition of Sm(NO3 )3 and Co(NO3 )2 to 320 nm SmCo‐O (SmCoO3 + Co3 O4 ) particles. A 5.8 g sample of SmCo3.8 ‐O particles was coated with CaO and then reduced at 900 °C by Ca to give 4.2 g of 260 nm SmCo5 particles. The SmCo5 particles are strongly ferromagnetic and the aligned particles in epoxy resin exhibit a large room‐temperature coercivity (Hc ) of 41.8 kOe and giant (BH)max (maximum magnetic energy product) of 19.6 MGOe, the highest value ever reported for SmCo5 made by chemical methods. This synthesis can be extended to synthesize Sm2 Co17 particles, providing a general approach to scaling up the synthesis of high‐performance Smx Coy nanomagnets for permanent magnet applications. Abstract : Spiel mit dem Feuer : Eine Flammenreaktion wird genutzt, um SmCo‐Oxid‐Partikel herzustellen, die anschließend zu stark ferromagnetischen Sm x Co y ‐Partikeln reduziert werden. Die 260‐nm‐SmCo5 ‐Partikel können in Epoxidharz eingebettet und ausgerichtet werden und zeigen dabei eine große Raumtemperatur‐Koerzitivkraft (Hc =41.8 kOe) und ein hohes magnetisches Energieprodukt (19.6 MGOe).